Efektivitas Instagram Sebagai Ruang Motivasi Hijrah Mahasiswa IAIN Lhokseumawe - Suhendar, Aris; Syam, Abdi Mubarak; Ritonga, Aulia Rahma (Talenta Publisher, 2023)
This study aims to look at the effectiveness of Instagram as a Space for Hijrah Motivation for IAIN Lhokseumawe Students. The various superior features that Instagram has make Instagram a promising interaction space, including influencers or preachers in delivering motivational messages. This paper is dissected using a qualitative methodology. The method used is descriptive qualitative method. The qualitative descriptive method examines the existing specific cases comprehensively, by identifying, describing, understanding, and interpreting the data obtained through the media. The results of the study show that Instagram has become a new instrument for social change, and is used by individuals and groups to create new social movements, including the hijrah movement. The increasing number of community leaders who have emigrated is one of the drivers of the increasing trend of migrating among students. The concept of hijrah among students is identified as one of the increasingly assertive trends in the social system of society. The use of Instagram as a media for preaching can bridge technological advances with the process of preaching, where users can access information about the Islamic world without time, cost and place constraints.